O mundo dos trabalhadores nas obras da década de 30 de John Steinbeck - Kölln, Lucas André Berno (2013)
This dissertation discusses the books of John Steinbeck published in the thirties, willing to comprehend the way that the dialogue between the author's literature and his dialectic relation with the historical reality in which he wrote and lived. The analysis of Steinbeck's writings produced during the thirties made possible the discussion about the effects of the 1929 crisis and the empowerment of monopolist capitalism, processes that became very evident in this period. The conflicts present in that reality molded the historical reading of the writer and of the social group that he centrally portrayed throughout his literary production, the small farmers. Steinbeck's deep connection with the old middle classes conditioned his literature and his worldview, since the writer was raised into that way of life and educated into the typical values of that social group. This made his literature, during the thirties, unfold itself in many different ways in order to deal with the experience of the destruction of that way of life in all of its complexity. As the crisis deepened, Steinbeck faced different expressions of it, being the proletarianization of the small farmers and the destruction of the basis of their world some of the most bruising aspects that his literature intended to expose, portray and denounce. Sometimes assuming nostalgic outlines to celebrate the past, sometimes drawing on the satire to question the bourgeois ethos, sometimes rising through the denounce to reveal the scars created by the economic transformations, Steinbeck did not duck the problems placed by the development of the American capitalism. Based on this, his literature has became not only an interpretation of the reality created by the Great Depression through its mechanisms, dynamics and structures, but also the literary testimony of a person who observed the decadence of the way of life in which he grew up and of his peers. In this sense, the dissertation aimed to situate and comprehend Steinbeck's writings in their historical concreteness, that is, in the terms in which they were conceived and produced, in such a way that it became possible to observe several dimensions of the crisis and of Steinbeck's historical reading related to this experience, marked by loss, by misery and by the transformation of the small farmers into agricultural workers